Anodized Ti6Al4V-ELI, electroplated with copper is bactericidal against Staphylococcus aureus and enhances macrophage phagocytosis - Paula Milena Giraldo-Osorno; Adam Benedict Turner; Sebastião Mollet Barros; Robin Büscher; Simone Guttau; Farah Asa’ad; Margarita Trobos; Anders Palmquist (Journal of Materials Science: Materials in Medicine)
Abstract Implants aim to restore skeletal dysfunction associated with ageing and trauma, yet infection and ineffective immune responses can lead to failure. This project characterized the microbiological and host cell responses to titanium alloy with or without electroplated metallic copper. Bacterial viability counting and scanning electron microscopy quantified and visualized the direct and indirect bactericidal effects of the Cu-electroplated titanium (Cu-Ep-Ti) against two different Staphylococcus aureus strains. Human THP-1 macrophage adhesion and viability was analyzed, along with phagocytosis. Results showed potent antimicrobial activity alongside promising host-immunomodulatory properties. Direct and indirect exposure to Cu-Ep-Ti produced potent bactericidal effects resulting in 94–100% reductions in bacterial viability at 24 h, with complete eradication in some cases. As expected, cytotoxicity was observed in THP-1 macrophages without media exchange, though when media was exchanged at 8, 24 and 48 h cell viability was equivalent to Control-Ti. Interestingly macrophages adhered to the copper material or grown in the presence of copper ions showed 7-fold increase in phagocytosis of S. aureus bioparticles compared to Control-Ti, suggesting a dual bactericidal and host immunomodulatory mechanism. In conclusion, this Cu-electroplated Ti biomaterial can limit bacterial contamination on the implant surface, whilst simultaneously promoting a beneficial antimicrobial immune response. Graphical Abstract